Effects of MS disease-modifying therapies on responses to vaccinations: A review - Ciotti, John Robert; Valtcheva, Manouela V.; Cross, Anne Haney (Multiple sclerosis and related disorders, 2020)
: Development of long-term immunologic memory relies upon humoral and cellular immune responses. Vaccinations aim to stimulate these responses against pathogens. Several studies have evaluated the impact of multiple sclerosis disease-modifying therapies on immune response to vaccines. Findings from these studies have important implications for people with multiple sclerosis who require vaccination and are using disease-modifying therapies. : Searches using PubMed and other engines were conducted in May 2020 to collect studies evaluating the impact of various disease-modifying therapies on immune responses to vaccination. : Several studies demonstrated preserved immune responses in people treated with beta-interferons to multiple vaccine types. Limited data suggest vaccine responses to be preserved with dimethyl fumarate treatment, as well. Vaccine responses were reduced to varying degrees in those treated with glatiramer acetate, teriflunomide, sphingosine-1-phosphate receptor modulators, and natalizumab. The timing of vaccination played an important role in those treated with alemtuzumab. Humoral vaccine responses were significantly impaired by B cell depleting anti-CD20 monoclonal antibody therapies, particularly to a neoantigen. Data are lacking on vaccine responses in patients with multiple sclerosis taking cladribine and high-dose corticosteroids. Notably, the majority of these studies have focused on humoral responses, with few examining cellular immune responses to vaccination. : Prior investigations into the effects of individual disease-modifying therapies on immune responses to existing vaccines can serve as a guide to expected responses to a SARS-CoV-2 vaccine. Responses to any vaccination depend on the vaccine type, the type of response (recall versus response to a novel antigen), and the impact of the individual disease-modifying therapy on humoral and cellular immunity in response to that vaccine type. When considering a given therapy, clinicians should weigh its efficacy against MS for the individual patient versus potential impact on responses to vaccinations that may be needed in the future.